Faktor Yang Berhubungan Dengan Pemanfaatan Puskesmas di Wilayah Kerja Puskesmas Amparita Kabupaten Sidenreng Rappang - M. Adnan Lira (Unit Publikasi Ilmiah Perkumpulan Intelektual Madani Indonesia, 2021)
Public health in the field of health policy administration is expected to be one of the supporting sectors in national health development in order to increase awareness, willingness, and ability to live healthy for everyone. This study is to identify the factors. This research was carried out at the Amparita Health Center, Sidenreng Rappang Regency, for 14 days starting from April 23 to May 6, 2020 by taking 357 samples. The data is processed and analyzed according to the research objectives. The results showed that there was a relationship between education and the use of health services with a calculated X2 value (50.513) > X2 table (3.841) or p-value (0.000) <0.05, there was a relationship between knowledge and the use of health services with a calculated X2 value (4.762). > X2 table (3.841) or p-value (0.029) <0.05 and there is a relationship between distance and utilization of health services with X2 count (50.159) > X2 table (3.841) or p-value (0.000) <0.05. It is recommended to heads of families who have less knowledge to be able to increase their knowledge about the importance of using health services by following counseling, both held by health workers and through electronic and print media.